Ejecución presupuestaria de gastos en el GAD Parroquial Rural de Ricaurte durante el periodo 2023. - Luque Granja, Ismael (2024)
During the 2023 period, the Rural Parish Autonomous Decentralized Government (GAD) of Ricaurte demonstrated efficient and transparent budget execution, fundamental for local development and community welfare. A literature review highlights that proper budget execution facilitates investment in essential infrastructure such as roads, water supply systems, sewage, educational centers, and health facilities. This investment directly contributes to human development and social welfare, ensuring equitable access to quality basic services such as education, health, housing, and culture. The verification of expenses incurred by the Rural Parish GAD of Ricaurte compared to the budget allocated revealed exact compliance in all budgetary items. Budgeted amounts matched actual expenses in each expenditure group, indicating precise execution without deviations. This consistency reflects responsible financial management aimed at maximizing the impact of allocated resources. Furthermore, the review of regulations and rules related to budget execution, through interviews with the GAD's accountant, showed a strong commitment to legal compliance. The GAD ensured compliance with relevant laws through the establishment of a supervisory team, implementation of effective internal controls, and periodic updating of manuals and internal procedures. Regular training and updates are conducted to ensure proper understanding and application of current regulations.